ANALISIS PONDASI BORE PILE DAN TIANG PANCANG TERHADAP BIAYA DAN WAKTU PENGERJAAN : Studi kasus: Pada Proyek Pembangunan Pangkalan Penjagaan Laut dan Pantai Kelas II Tanjung Perak - Alifiandi Varian Jaya; Michella Beatrix; Putri Suci Mawariza (LPPM Universitas Bina Bangsa, 2023)
The current development in the construction industry is rapidly advancing. Regardless of any construction process, it takes a considerable amount of time to complete from start to finish. Therefore, careful considerations are needed to determine the most appropriate and efficient way to execute a construction project. Tanjung Perak Class II Sea and Coastal Guard Base (Pangkalan Penjaga Laut dan Pantai or PLP) is a Technical Implementation Unit under the authority and responsibility of the Directorate General of Sea Transportation, as regulated by the Ministry of Maritime Affairs. In this project, pile foundation is being used. However, during the foundation work, several challenges arise. These include the unavailability of ready-to-use hydraulic equipment, hydraulic equipment repairs, and a one-week delay in the arrival of the pile foundation, which leads to a delay in the foundation work. As a result, the workers cannot maximize their productivity while waiting for the equipment to arrive. In addition to the delay, there is also a cost escalation, as the workers are still being paid despite not being able to work at their maximum capacity. Therefore, a comparison between the current pile foundation and alternative foundation types is necessary to find a more efficient solution and minimize the encountered challenges. Based on the data analysis, the duration required for the preparation work and the installation of 65 points of 30x30cm pile foundation with a depth of 16m at Tanjung Perak Class II Sea and Coastal Guard Base is 8 weeks or 56 days, with a cost of Rp 670,742,965.00. On the other hand, the duration for the preparation work and the installation of 65 points of 30cm bore pile foundation with a depth of 16m is 69 days or 10 weeks, with a cost of Rp 520,779,603.00. From the discussions and deliberations above, the time difference between pile foundation and bore pile foundation is 13 days. Bore pile foundation takes 13 days longer than pile foundation. The cost difference between pile foundation and bore pile foundation is Rp 149,963,362